Math, asked by BrainIyMSDhoni, 1 year ago

Solve the question please
No spam please ​

Attachments:

Answers

Answered by BrainlyConqueror0901
37

{\bold{\underline{\underline{Answer:}}}}

{\bold{\therefore \int   \limits_{ 0 }^{ \frac{\pi}{4} }  ln(1 +  tan \: x) dx=\frac{\pi}{8}\:ln(2)}}

{\bold{\underline{\underline{Step-by-step\:explanation:}}}}

 \underline  \bold{given : } \\  \implies  \int   \limits_{ 0 }^{ \frac{\pi}{4} }  ln(1 +  tan \: x) dx \\  \\  \implies  \bold{let} \:  \:   \int   \limits_{ 0 }^{ \frac{\pi}{4} }  ln(1 +  tan \: x) dx  = I \\  \\  \implies  \bold{x =  ( \frac{\pi}{4}  - y) =  > dx =  - dy }\\  \\   \implies   - \int   \limits_{  \frac{\pi}{4}  }^{ 0 }  ln(1 +  tan \: ( \frac{ \pi }{4}  - y)) dy \\  \\  \implies  \int   \limits_{ 0 }^{ \frac{\pi}{4} }  ln(1 +  tan \:  (\frac{ \pi }{4}  - y)) dy \\  \\  \bold {tan (A  -  B) =  \frac{tan \: A - tan \: B}{1 + tan \:A  \times tan \: B} } \\  \\  \implies tan( \frac{\pi}{4}  - y) =  \frac{tan \frac{\pi}{4} - tan \: y }{1 + tan \frac{\pi}{4} \times tan \: y}  \\  \\ \bold { \implies tan( \frac{\pi}{4}  - y)  =  \frac{1 - tan \: y}{1 + tan \: y} } \\  \\  \bold{ putting \: value \:of \: tan( \frac{\pi}{4}  - y) } \\  \\  \implies \int   \limits_{ 0 }^{ \frac{\pi}{4} }  ln(1 +  tan \:  (\frac{ 1 - tan \: y }{1 + tan \: y} )) dy

\implies \int   \limits_{ 0 }^{ \frac{\pi}{4} }  ln(1 +   \: \frac{ 1 - tan \: y }{1 + tan \: y} ) dy  \\  \\  \implies \int   \limits_{ 0 }^{ \frac{\pi}{4} }  ln( \frac{1 + \cancel{ tan \: y} + 1  \cancel{-  \: tan \: y}}{1 +  \: tan \: y} ) dy \\  \\  \implies  \int   \limits_{ 0 }^{ \frac{\pi}{4} }  ln( \frac{2 }{1 + tan \: y} ) dy \\  \\     \bold{ln (\frac{A}{B} ) = ln \: A - ln \: B} \\  \\ \implies \int   \limits_{ 0 }^{ \frac{\pi}{4} } ( ln(2) -  ln(1 + tan \: y))dy \\  \\  \implies \int   \limits_{ 0 }^{ \frac{\pi}{4} }  ln(2) dy-  \int   \limits_{ 0 }^{ \frac{\pi}{4} }  ln(1 + tan \: y)dy \\   \\  \implies  \int   \limits_{ 0 }^{ \frac{\pi}{4} } ( ln(2) dy- I

 \implies ln(2)   [y]_{0}^{ \frac{\pi}{4} }  - I\\  \\  \implies ln(2)( \frac{\pi}{4}  - 0) - I\\  \\  \implies I =  \frac{ \pi }{4} \: ln(2) - I\\   \\  \implies 2  I =  \frac{\pi}{4}  \: ln(2) \\  \\  \implies I =  \frac{\pi}{8}  \: ln(2)  \\   \\   \bold{\implies  \frac{\pi}{8}  \: ln(2)}

{\bold{\therefore \int   \limits_{ 0 }^{ \frac{\pi}{4} }  ln(1 +  tan \: x) dx=\frac{\pi}{8}\:ln(2)}}

Answered by Anonymous
3

Step-by-step explanation:

hope it helps you good morning

Attachments:
Similar questions